"Are you a good witch or a bad witch?" An exercise in suspending judgment when interacting with "difficult" people. Issue 1 (2nd January 2020) - Seiter, John S.; Seiter, Christian R.
ABSTRACT: Courses: Interpersonal Communication, Health Communication Objectives: In this single-class activity, students gain awareness and practice in suspending judgments about "difficult" people in order to understand the reasoning behind certain objectionable behavior.